Administrative-territorial reform: results of integration of the consolidated territorial communities (CTC) in the Khmelnytsky region - Melnychuk, Anatoliy; Melnyk, Tetiana (Human Geography Journal, 2017)
The article reviews the changes in administrative-territorial division of the Khmelnytsky region that occurred due to the reform of the territorial organization of power inUkraine. The authors have given an assessment of the methodic of formation of the territorial communities capable for social and economic development, analyzed the definition of the territorial community capable for social and economic development, and defined the requirements for creation of the necessary infrastructure for community development. Consolidated territorial communities, created in the Khmelnytsky region, were divided into groups in terms of their economic capacity. The article also presents specific achievements of the consolidated territorial communities over the year 2016.The authors pointed out the least and most dependent communities on the state budget, separately distinguishing the communities functioning as donors of the state budget, and analyzed the communities in terms of their own budget profits per capita. It was defined that creation of the consolidated territorial communities in most cases resulted in duplication of budget revenues per capita. However, economic viability of the newly created consolidated territorial communities is quite irregular: communities that have a large territory with a small number of people and are situated in remote areas of the region have a considerably lower own income per capita.